Natural product nobiletin-loaded Pickering emulsion stabilized by bovine serum albumin/carboxymethyl inulin complexes: preparation and digestive characteristics - Huang, Guiying; Zhang, Man; Feng, Konglong; Xiao, Jie; Huang, Qingrong; Ho, Chi-Tang; Liu, Jun (Frontiers in Pharmacology, 2024)
To expand the application of nobiletin (NOB) in semi-solid functional foods, bovine serum albumin (BSA)/carboxymethyl inulin (CMI) complexes-stabilized Pickering emulsion (BCPE) (φoil = 60%, v/v) was fabricated, and the swallowing index and bioavailability of the NOB-loaded Pickering emulsion was evaluated. Confocal laser scanning microscope (CLSM) and cryo-scanning electron microscopy (cryo-SEM) images revealed that BSA/CMI complexes attached to the oil–water interface. NOB-loaded BCPE exhibited a viscoelastic and shear-thinning behavior. Fork drip test results suggested that the textural value of unloaded and NOB-loaded emulsions was International Dysphagia Diet Standardisation Initiative Level 4, which could be swallowed directly without chewing. The in vitro lipolysis model suggested that NOB had a faster digestive profile and a higher bioaccessibility in the BCPE than in the oil suspension. The in vivo rat model revealed that the oral bioavailability of NOB was increased by 2.07 folds in BCPE compared to its bioavailability in unformulated oil. Moreover, BCPE led to a higher plasma concentration of the major demethylated metabolite of NOB (4′-demethylnobiletin) than the unformulated oil. Accordingly, BCPE enhanced the oral bioavailability of NOB by improving bioaccessibility, absorption, and biotransformation.